STRATEGI DIPLOMASI EKONOMI INDONESIA DALAM MEMAJUKAN PEMBANGUNAN EKONOMI NASIONAL MELALUI KEPEMIMPINAN INDONESIA DALAM FORUM G-20 TAHUN 2022 - Yoshida, Yeni Herliana; Kriswandwitanaya, Muhammad Farhan (Global Mind, 2023)
This article discusses the role of Indonesia's economic diplomacy in national economic development through the G20 Presidency in 2022. As a member and host of the G20, Indonesia has the opportunity to strengthen partnerships, boost productivity and enhance sustainable economic growth. This article focuses on Indonesia's five main pillars as the G20 Presidency and the six priority agendas in financial track to be discussed. It also emphasizes how economic diplomacy fulfills Indonesia's national interest in economic development. The importance of the G20 in supporting the international development agenda, especially the Sustainable Development Goals (SDGs) which includes goal 8 on decent work and     economic growth, is also emphasized. As a member of the G20, Indonesia is committed to implementing SDGs programs and paying attention to its targets, including per capita economic growth, increased productivity, development- oriented policies, and world resource efficiency. Indonesia's 2022 G20 presidency, with the theme "Recover Together, Recover Stronger" is an opportunity to strengthen Indonesia's economic diplomacy and build the nation's image. This article highlights Indonesia's foreign policy measures that focus on economic diplomacy to achieve national interests. In this context, the role of Indonesia's economic diplomacy during the 2022 G20 Presidency is the focus of this article.